Graphic designer as curator: from a problem-solver to a problematiser - Tang, Junie Tze Yin (Nanyang Technological University, 2023)
Problems brought on by climate change, ageing populations, and pestilences like COVID-19 are causing the world to become more troubled than it ever was, and notably, a small city-state like Singapore is not spared from these calamities. As more government and social agencies are seeking creative solutions to tackle these problems and improve people’s quality of life through design, this study asks: How can Singapore’s graphic designers interrogate their conventional role as problem-solvers and go beyond the use of Design Thinking, which is a problem-solving approach, to address challenging social problems that are deemed as “wicked”? In seeking an answer to this central questions through the lenses of theory and praxis, this research responds to the call of an interdisciplinary approach by the Ministry of Education (Singapore) and explores the concept of transdisciplinary advocated by the West to fulfil its aim of outlining an alternative role for local graphic designers, which would allow them to approach seemingly boundless socio-political challenges in a more sustainable manner. In theory, this study is guided by a research framework that first traces the genealogy of design as a problem-solving activity, then explains how societal problems are “wicked” and why Design Thinking might not be sufficient for graphic designers to address them. Next, with more Singaporean institutions and organisations expressing a strong interest in an interdisciplinary approach in learning and practice, this study then turns to a different field – curatorial practice – in search of an alternative role. Paulo Freire’s and Michel Foucault’s theories on problematisation are explored, to shed light on a feasible transdisciplinary approach that graphic designers could adopt to effect positive social change. Acknowledging that the concept of “graphic designers as curators” is not new, this study investigates how it has been applied by various graphic designers to connect art and the public, establish the concept of “meta design-authorship”, and expand graphic design practice. Through Christopher Alexander’s theory of an unselfconscious and self-adjusting process, Critical Design emerges as a form of problematisation that allows graphic designers to keep cycling back to complex design problems critically and relentlessly via the medium of exhibitions. In practice, the examination of three case studies – Metahaven, Supernormal and Atelier HOKO, outlines the characteristics of a new generation of graphic designer-curators based overseas, and more importantly, in Singapore. All things considered, the findings of this study produce new knowledge that contributes to the field of graphic design by putting forward a revitalised notion of graphic designers as curators who are also problematisers in theory, offering a feasible transdisciplinary approach that allows local graphic designers to positively impacts to their communities in a sustainable manner.